Analisis Faktor-faktor yang Mempengaruhi Minat Mahasiswa Dalam Karir Akuntan Publik dan Akuntan Non Publik (Studi Perbandingan Pada Universitas Muhammadiyah Surakarta dan Universitas Sebelas Maret Surakarta) - Baraba, robiyah thoriq, Fauzan, SE., M.Si (2015)
This research purposes: (1) to analysis differencing and influence financial rewar or wage, professional trainning, confession professional, social values, work environment, market consideration and personality to choosen carreer of students accounting economic department to be public accountant and non public accountang. (2) To analysis differencing variables financial rewar or wage, professional trainning, confession professional, social values, work environment, market consideration and personality to choosen carreer of students accounting economic department of Muhammadiyah University of Surakarta and Sebelas Maret University of Surakarta. Research method uses descriptive method with survey by spreading quetionnaire to collecting data. Sum sample of this research is 142 respondens. Analysis tool uses logistic analysis and man whitney test (hypothesis test). Man whithney test research result shows differencing variables confession professional, social values, work environment and market consideration to student's desire to be public accountant and non public, variables financial reward, professional training and personality are not differencing to students desire to be public accountant and non public. Variables students perception about wage, professional trainning, professional confession, social values, market consideration and personality are differencing between UNS and UMS, variable work environment is not differencing between students UNS and UMS. Variables financial reward/wage and personality significant influence to student's desire to be public accountant and non public. Variables trainning professional, professional confession professional, work environment, market consideration are not significant influence to student's desire to be public accountant and non public. Variable social value significant influeces to student's desire to be public accountang and non public. Keyword: Financial reward or wage, professional trainning, professional confession, social values, work environment, market consideration, personality, public accountang, non public accountant.